Mast cells in newly formed lining tissue during acute inflammation: a six day air pouch model in the mouse. - Sin, Y M (1986)
Connective tissue mast cells were topographically and quantitatively studied in the newly formed lining tissue of six day old air pouches induced in the dorsal surface of mice. The results showed that the number of mast cells in the cavities innermost lining increased after injection of carrageenan into the cavity. Degranulation of mast cells was also observed. Variations in mast cell numbers in the lining seemed to correlate with the histamine content. These findings suggest that mast cells not only participate in the initiation of the early phase of acute inflammation but also appear to play an important part in regulating and prolonging more chronic inflammatory reactions.